Reference Standards for C-Peptide in Korean Population: A Korean Endocrine Hormone Reference Standard Data Center Study - Cho, Jooyoung; Cho, Ho-Chan; Ryu, Ohk-Hyun; Kim, Hyo-Jeong; Kim, Chang Geun; Yun, Young Ran; Chung, Choon Hee (Endocrinology and metabolism (Seoul), 2024)
Background: The Korean Endocrine Hormone Reference Standard Data Center (KEHRS DC) has created reference standards (RSs) for endocrine hormones since 2020. This study is the first of its kind, wherein the KEHRS DC established RSs for serum Cpeptide levels in a healthy Korean population.Methods: Healthy Korean adults were recruited from May 2021 to September 2023. After excluding participants according to our criteria, serum samples were collected; each participant could then choose between fasting glucose only or fasting glucose plus an oral glucose tolerance test (OGTT). If their sample showed high glucose (≥100 mg/dL) or hemoglobin A1c (HbA1c) (≥5.70%), their C-peptide levels were excluded from analyzing the RSs.Results: A total of 1,532 participants were recruited; however, only the data of 1,050 participants were analyzed after excluding those whose samples showed hyperglycemia or high HbA1c. Post-30-minute OGTT data from 342 subjects and post-120-minute OGTT data from 351 subjects were used. The means±2 standard deviations and expanded uncertainties of fasting, post-30-minute and 120-minute OGTT C-peptide levels were 1.26±0.82 and 0.34–3.18, 4.74±3.57 and 1.14–8.33, and 4.85±3.58 and 1.25–8.34 ng/mL, respectively. Serum C-peptide levels correlated with obesity, serum glucose levels, and HbA1c levels.Conclusion: The RSs for serum C-peptide levels established in this study are expected to be useful in both clinical and related fields.